Pengembangan Bahan Ajar Berbasis Kearifan Lokal Padang Lawas untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa Kelas IV SD - Muhammad Khoiron Nasution; Sukmawarti Sukmawarti; Hidayat Hidayat (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to develop Local Wisdom-Based Teaching Materials for Grade IV Elementary School Students in Padang Lawas. This study is a research and development (Research and Development) using the ADDIE development procedure consisting of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The instrument used to collect data is a questionnaire given to several expert reviewers, namely material expert reviewers, teaching material expert reviewers, teacher responses and student responses. The validation score obtained from the material expert reviewer is 90. Open material experts are 91. Teacher responses are 95.7 and student responses are 96.3. From these scores, it can be said that the Local Wisdom-Based Teaching Materials for Padang Lawas that have been developed are "Very Valid" for use in the learning process. From the results of the implementation, it is known that there has been an increase in the learning outcomes of grade IV elementary school students after using the developed teaching materials. The overall score of students' grades after using Padang Lawas Local Wisdom-Based Teaching Materials is 82. At the evaluation stage, the average score obtained from all experts is 93.25. From this score, it can be said that the Padang Lawas Local Wisdom-Based Teaching Materials for Grade IV Elementary School that were developed are "Very Valid" for use in the learning process